Russian Policy Towards Jerusalem - E. O. Shebalina (Vestnik MGIMO-Universiteta)
Book review: A.V. Krylov, A.V. Fedorchenko, V.M. Morozov. Jerusalem: history, demography, economy and Russian policy towards the Holy City. Moscow: MGIMO-University, 2022. 370 p.